Planning of sport and recreational facilities informed by interdisciplinary knowledge: An attempt to make a systematic and transparent design strategy. (15th July 2019) - Hjort, Mikkel; Martin, W. Mike; Troelsen, Jens
Abstract : Purpose: The purpose of this paper is to develop a design strategy that investigates the systematic use of interdisciplinary knowledge through a transparent decision-making process. The study identifies relevant design parameters that should be considered in the development of this design strategy. Design/methodology/approach: The empirical data were collected through observations of the design process of two new sport facilities, meetings with sport, well-being and aging experts and through semi-structured interviews with end-users. The development of the proposed design strategy is based on a methodology with elements from "Knowledge to Action (KTA), " "Action research" and a "List of value concepts." The rigid timetable guaranteed systematic progress, where both knowledge from the end-users and experts were incorporated throughout the decision-making process. Findings: The two case studies documented results involving end-users and experts in a systematic way. In conclusion, it was apparent that the use of interdisciplinary collaboration informed the design outcome. Practical implications: Based on the two cases, the following advice can be given to the architectural profession: architects should use the KTA model or similar in order to target the search for relevant interdisciplinary knowledge and ensure that relevant evidence is involved in the design process of upcoming projects regarding sport and recreation. Architects should make the design process transparent so that one can see which design decisions have been made through the design process. This must be done to ensure that there is greater coherence between vision and practice. Originality/value: The study showed how architects could import knowledge, skills and values from other disciplines such as environmental psychology and active living research to improve the decision-making process of future sport and recreation projects. It was also clear that this design decision process could be made more transparent in the effort to allow the various stakeholders to take ownership of the resulting design outcomes.